Soil: the great connector of our lives now and beyond COVID-19 - Poch, R.M.; Anjos, L.H.C. dos; Attia, F.; Balks, M.; Benavides-Mendoza, A.; Bolanos-Benavides, M.M.; Calzolari, C.; Chabala, L.M.; Ruiter, P.C. de; Francke-Campana, S.; Prechac, F.G.; Graber, E.R.; et al. (Copernicus GmbH, 2020)
Humanity depends on the existence of healthy soils, both for the production of food and for ensuring a healthy, biodiverse environment, among other functions. COVID-19 is threatening food availability in many places of the world due to the disruption of food chains, lack of workforce, closed borders and national lockdowns. As a consequence, more emphasis is being placed on local food production, which may lead to more intensive cultivation of vulnerable areas and to soil degradation. In order to increase the resilience of populations facing this pandemic and future global crises, transitioning to a paradigm that relies more heavily on local food production on soils that are carefully tended and protected through sustainable management is necessary. To reach this goal, the Intergovernmental Technical Panel on Soils (ITPS) of the Food and Agriculture Organization of the United Nations (FAO) recommends five active strategies: improved access to land, sound land use planning, sustainable soil management, enhanced research, and investments in education and extension.